2010
DOI: 10.1603/ec09317
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Emergence Traps for Monitoring Blueberry Gall Midge (Diptera: Cecidomyiidae) Adults and Within Field Distribution of Midge Infestation

Abstract: The blueberry gall midge, Dasineura oxycoccana (Johnson) (Diptera: Cecidomyiidae), is a key pest of rabbiteye blueberry, Vaccinium virgatum Aiton, in the southeastern United States, but it has not been studied extensively and little is known about its ecology and management. Studies were conducted to develop an improved method for monitoring D. oxycoccana adults and to determine the within-field distribution of infestation. Four emergence traps were evaluated in an organic rabbiteye blueberry planting for thei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 15 publications
1
18
0
Order By: Relevance
“…Although the occurrence of female-biased sex ratio has been repeatedly observed in various species of gall midges (Matuszewski 1982;McClay 1996;Dorchin and Freidberg 2004;Rajamani et al 2004;Shahu et al 2004;Smith et al 2004;Ogah et al 2010), some studies, focusing on the precise sex ratio at the time of emergence, have revealed an equal or almost equal number of male and female progenies in the populations (Baxendale and Teetes 1981;Mo and Liu 2007;Roubos and Liburd 2010). This means that the estimated sex ratio in natural populations is not directly applicable to the time of reproduction or even the time of adult emergence.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the occurrence of female-biased sex ratio has been repeatedly observed in various species of gall midges (Matuszewski 1982;McClay 1996;Dorchin and Freidberg 2004;Rajamani et al 2004;Shahu et al 2004;Smith et al 2004;Ogah et al 2010), some studies, focusing on the precise sex ratio at the time of emergence, have revealed an equal or almost equal number of male and female progenies in the populations (Baxendale and Teetes 1981;Mo and Liu 2007;Roubos and Liburd 2010). This means that the estimated sex ratio in natural populations is not directly applicable to the time of reproduction or even the time of adult emergence.…”
Section: Discussionmentioning
confidence: 99%
“…According to previous studies, the sex ratio of gall midges tends to be almost 1:1 when it is calculated just at the time of adult emergence using methods that prevent emerging individuals from dispersal (Baxendale and Teetes 1981;Smith et al 2004;Mo and Liu 2007;Roubos and Liburd 2010); however, by direct sampling from natural populations, a female-biased sex ratio is usually estimated (Havelka and Zemek 1999;Dorchin and Freidberg 2004;Rajamani et al 2004;Smith et al 2004;Dorchin et al 2007). This contradiction between various studies shows that some secondary factors are involved in sex ratio biases from the primary sex ratio (1:1) after the appearance of adult gall midges in nature.…”
Section: Introductionmentioning
confidence: 99%
“…Peaks of emergence and infestation occurred through July and August. In Florida, where blueberry gall midge is an economically important pest of rabbiteye blueberry, initial catches can occur as early as 14 January, with peak adult emergence on 21 March (Roubos and Liburd 2010a). There, the growing and harvest season are much earlier than in Michigan.…”
Section: Discussionmentioning
confidence: 99%
“…In 2010 and 2011, emergence traps similar to those tested by Roubos and Liburd (2010a) were deployed within the same four Þelds in which the yellow sticky traps were placed. In 2010, from 9 April to 23 August, 12 emergence traps were retrieved and replaced once per week at each farm, and the number of blueberry gall midge adults trapped in the petri dish was counted.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation